Globally correlated conformational entropy underlies positive and negative cooperativity in a kinase’s enzymatic cycle - Yingjie Wang (Nature Portfolio, 2019)
Allosteric interactions are an important contributor to the catalytic properties of enzyme. Here the authors demonstrate—using the prototypical protein kinase PKA—that the allosteric cooperativity underscoring substrate recognition and product release are directly linked to changes in conformational entropy.